Wear-resistant cobalt-based alloy and method for producing same

CN123027481APending Publication Date: 2026-11-03HEBEI DAHE MATERIAL TECH CO LTD +2
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202611225730.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-13
Publication Date
2026-11-03

AI Technical Summary

Technical Problem

Traditional cobalt-based alloy preparation processes suffer from problems such as single heat treatment, uneven distribution of precipitates, coarse grains, poor strength-toughness matching, low surface hardness, and easy wear and peeling. Existing technologies are unable to achieve significant results in improving the wear resistance of alloys.

Method used

An integrated manufacturing process is adopted, which includes vacuum induction melting, homogenization heat treatment, temperature-controlled forging, gradient hot rolling, clean pickling, precision cold rolling, and stress-relief annealing. Combined with precise control of chemical composition ratio and full-process heat treatment parameters, the homogenization of alloy structure and the improvement of performance are achieved.

Benefits of technology

It significantly improves the room temperature hardness and wear resistance of cobalt-based alloys. The room temperature hardness of the alloy reaches ≥500 HV10, and the wear rate is 0.8×10-5~1.2×10-5 mm³/(N·m), which solves the problems of low hardness and poor wear resistance in traditional processes.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN123027481A_ABST
    Figure CN123027481A_ABST
Patent Text Reader

Abstract

The application discloses a wear-resistant cobalt-based alloy and a preparation method thereof. The chemical composition of the cobalt-based alloy is as follows: Ni: 22-35%, Cr: 8-12%, Mo: 3-9%, Ti: 0.1-1.5%, Fe: 1-2%, Al: 0.3-2.5%, Nb: 0.5-1.5%, C: less than or equal to 0.06%, B: less than or equal to 0.01%, P: less than or equal to 0.02%, Mn: less than or equal to 0.2%, and the rest is Co and inevitable impurities. The preparation method comprises vacuum induction smelting, homogenization heat treatment, controlled temperature forging breakdown, gradient hot rolling forming, pickling, cold rolling, stress relief annealing and solid solution aging treatment. The cobalt-based alloy has good wear resistance and organizational stability, the room temperature hardness is greater than or equal to 500 HV10, the room temperature wear rate is 0.8*10 ‑5 -1.2*10 ‑5 mm 3 / (N*m).
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of cobalt-based alloy preparation technology, specifically relating to a wear-resistant cobalt-based alloy and its preparation method. Background Technology

[0002] Cobalt-based alloys, with their excellent comprehensive properties, are widely used in key fields such as aerospace, machinery manufacturing, metallurgy, and chemical engineering. Especially under harsh operating conditions of high temperature, high load, and strong wear, the performance of alloy components directly determines the operational stability, reliability, and service life of equipment. However, traditional preparation processes have drawbacks: the heat treatment process is limited, resulting in uneven distribution of precipitates, coarse grains, poor strength-toughness matching, low surface hardness, and susceptibility to wear and spalling.

[0003] Patent application CN 118835186 A discloses a cobalt-based superalloy with anti-adhesive wear, a key shaft, and a method for preparing the alloy. It proposes a process scheme of "multi-directional forging + secondary homogenization heat treatment" to obtain uniform and fine grains and uniformly distributed carbides, providing a clear technical path for improving the wear resistance of the alloy. However, relying solely on forging modification, the grain refinement effect is limited, and oxide scale and defects are easily formed on the surface of the billet, which will aggravate abrasive wear.

[0004] Patent application CN 121653641 A discloses a high-temperature wear-resistant cobalt-based alloy coating without metallurgical defects, its preparation method and application. Its advantages are that a protective layer can be quickly formed on the alloy surface, and the coating material can be flexibly adjusted according to simple working conditions. However, it only provides surface coating protection and does not optimize the matrix structure and bulk properties. After long-term service, the coating is prone to peeling and cracking, which limits its service life. Powder deposition molding is prone to leaving hidden metallurgical defects such as micropores and microcracks, resulting in poor structural stability. Summary of the Invention

[0005] The purpose of this invention is to provide a wear-resistant cobalt-based alloy and its preparation method. By adopting an integrated preparation process that includes vacuum induction melting, homogenization heat treatment, temperature-controlled forging, gradient hot rolling, clean pickling, precision cold rolling, stress-relief annealing combined with solution aging, the invention solves the problems of insufficient room temperature hardness, low wear rate, and uneven microstructure of existing cobalt-based alloys. Furthermore, by precisely controlling the chemical composition ratio and the parameters of the entire heat treatment process, the invention achieves a synergistic improvement in the room temperature hardness and wear resistance of the alloy.

[0006] To achieve the above objectives, the present invention adopts the following technical solution: A wear-resistant cobalt-based alloy has the following chemical composition and mass percentage: Ni: 22-35%, Cr: 8-12%, Mo: 3-9%, Ti: 0.1-1.5%, Fe: 1%-2%, Al: 0.3-2.5%, Nb: 0.5-1.5%, C≤0.06%, B≤0.01%, P≤0.02%, Mn≤0.2%, with the remainder being Co and unavoidable impurities.

[0007] Furthermore, the chemical composition of the cobalt-based alloy of the present invention satisfies: 0.1≤Ti / Al≤0.2, 1.5%≤Fe+Nb≤3%, B+P≤0.02%.

[0008] With a Ti / Al ratio of 0.1 ≤ Ti / Al ≤ 0.6, Al improves the matrix hardness and wear resistance; Ti refines the grains, improves the distribution of precipitated phases, and synergistically stabilizes the internal microstructure. If the Ti / Al ratio is too low, the grain refinement effect is insufficient, leading to coarse aggregation of reinforcing phases, uneven microstructure, reduced hardness, and a significant decrease in wear resistance. If the ratio is too high, excess titanium can easily form brittle and harmful phases, generating residual stress and inducing rolling microcracks and surface defects. Strictly controlling this ratio can effectively improve long-term wear resistance.

[0009] With Fe+Nb controlled at 1.5% to 3%, it can achieve efficient strengthening through solid solution and hardening synergy, ensuring sufficient hardness and resistance to abrasive wear, while avoiding excessive total addition which would cause coarse microstructure and increased brittleness, thus preventing chipping and spalling during wear.

[0010] The ratio of B+P ≤ 0.02% is because both are prone to segregation at grain boundaries. Excessive amounts will significantly reduce grain boundary bonding, leading to thermal embrittlement and wear spalling. By controlling the total amount, the grain boundary strengthening effect of B can be utilized while minimizing the risk of impurity embrittlement, thus balancing the alloy's toughness and wear resistance reliability.

[0011] The method for preparing the wear-resistant cobalt-based alloy of the present invention includes the following steps: S1. Vacuum induction melting and casting into vacuum ingots.

[0012] S2. Demold the ingot obtained in S1 and perform homogenization heat treatment.

[0013] S3. Forge the ingot after S2 heat treatment into an intermediate billet; S4. Roll the intermediate billet obtained in S3 into a sheet.

[0014] S5. Perform acid pickling treatment on the board surface of the board obtained in S4.

[0015] S6. The plate after S5 pickling is cold rolled.

[0016] S7. Anneal the S6 cold-rolled sheet.

[0017] S8. After S7 annealing, the board is subjected to solution aging treatment.

[0018] Furthermore, in step S2, the homogenization heat treatment involves a furnace loading temperature ≥ 500°C. After the ingot is placed in the furnace, the temperature is raised to 800°C–850°C at a rate of 80–150°C / h and held for 5–8 hours. Subsequently, the temperature is raised to 1050–1100°C at a rate of 50–100°C / h and held for 10–20 hours.

[0019] Furthermore, in step S3, the forging process has an initial forging temperature of 1150–1190°C, a final forging temperature of ≥900°C, and a total forging reduction of 60%–75%.

[0020] Further, in step S4, the intermediate billet is heated to 1000-1050°C and rolled continuously in multiple passes to obtain a hot-rolled finished plate with a thickness of 2.0-6.0 mm.

[0021] Furthermore, in step S5, the pickling is carried out at a temperature of 38–60°C for 3–8 minutes, followed by high-pressure water rinsing and hot air closed-loop drying to remove oxide scale and surface residues.

[0022] Furthermore, the annealing described in step S7 is carried out at a temperature of 650–750°C for 2–4 hours, followed by slow cooling in the furnace.

[0023] Further, in step S8, the solution aging treatment involves heating the annealed board from S7 to 900–1000°C, holding it at that temperature for 1–2 hours, and then water-cooling it to room temperature. The first stage of aging is then performed, holding the board at 300–380°C for 3–5 hours, followed by furnace cooling to room temperature. The second stage of aging is then carried out, holding the board at 520–600°C for 4–8 hours, and finally furnace cooling to room temperature.

[0024] The inventive principle of this invention lies in: This invention creatively employs a core technical approach of precise elemental ratio control coupled with a full-process coupled strengthening process. It optimizes and limits the ratio of Ni, Cr, and Mo, the main elements, to construct a high-strength solid solution matrix; achieving coupled fine-grain strengthening and precipitation strengthening, while avoiding defects such as grain boundary embrittlement and rolling cracks caused by excessive amounts of a single element, thus optimizing the wear-resistant matrix of the alloy from the compositional source. Simultaneously, it integrates vacuum melting, stepped homogenization treatment, temperature-controlled forging and hot rolling, stress-relief annealing, and a two-stage solid solution aging process to eliminate as-cast segregation and residual processing stress, thereby improving the alloy's resistance to spalling.

[0025] The beneficial effects of adopting the above technical solution are as follows: This invention employs an integrated process encompassing vacuum induction melting, homogenization heat treatment, forging, hot rolling, pickling and cleaning, cold rolling, annealing, and solution aging. This effectively improves the purity of the cobalt-based alloy matrix, eliminating ingot composition segregation, internal porosity, and residual rolling stress. It precisely matches key process parameters for each step, refining the alloy's microstructure and creating a uniform grain structure, effectively addressing the defects of traditional sheet metal, such as low hardness, poor wear resistance, and uneven microstructure. This synergistically enhances the room temperature hardness and overall wear resistance of cobalt-based alloy sheets.

[0026] This invention achieves an alloy with a room temperature hardness ≥500 HV10 and a room temperature wear rate of 0.8 × 10⁻⁶ through integrated and synergistic control of composition design and preparation process. -5 ~1.2×10 -5 mm 3 / (N·m). Attached Figure Description

[0027] Figure 1 This is a SEM image of the surface morphology of the alloy obtained in Example 3.

[0028] Figure 2 This is a metallographic grain structure diagram of the alloy obtained in Example 3.

[0029] Figure 3 This is a laser confocal morphology image of the alloy obtained in Example 3. Detailed Implementation

[0030] The technical solution of the present invention will be further described in detail below through embodiments.

[0031] Examples 1-7 and Comparative Examples 1-2 The chemical composition of the cobalt-based alloys in each embodiment and comparative example is shown in Table 1.

[0032] Table 1. Chemical composition (%) of cobalt-based alloys in each embodiment and comparative example

[0033] The preparation methods of cobalt-based alloys in each embodiment include the following steps: S1. Vacuum induction melting: Select cobalt, chromium, nickel and other metal raw materials with a purity of ≥99.95%, weigh them accurately according to the composition in Table 1, and cast them into vacuum ingots after vacuum induction melting.

[0034] S2. Demold the ingot obtained in S1 and perform homogenization heat treatment. The furnace loading temperature is ≥500℃. The ingot is put into the furnace and heated to 800℃~850℃ at a rate of 80~150℃ / h and held for 5~8h. Then, the temperature is raised to 1050~1100℃ at a rate of 50~100℃ / h and held for 10~20h.

[0035] S3. Forge the ingot after S2 heat treatment into an intermediate billet. The initial forging temperature is 1150-1190℃, the final forging temperature is ≥900℃, and the total forging reduction is 60%-75%.

[0036] S4. Roll the intermediate billet obtained in S3 into a plate. Specifically, heat the intermediate billet to 1000-1050℃ and roll it continuously in multiple passes to obtain a hot-rolled finished plate with a thickness of 2.0-6.0 mm.

[0037] S5. The board obtained in S4 is pickled at a temperature of 38-60℃ for 3-8 minutes, followed by high-pressure rinsing with clean water and hot air closed-loop drying to remove oxide scale and surface residue.

[0038] S6. The plate after S5 pickling is cold rolled.

[0039] S7. Anneal the S6 cold-rolled sheet at a temperature of 650-750℃ for 2-4 hours, and then slowly cool it in the furnace.

[0040] S8. After S7 annealing, the board is subjected to solution aging treatment. The board is heated to 900-1000℃ and held for 1-2 hours, then water-cooled to room temperature. The first stage of aging is carried out, and the board is held at 300-380℃ for 3-5 hours, then furnace-cooled to room temperature. The second stage of aging is then carried out, and the board is held at 520-600℃ for 4-8 hours, and finally furnace-cooled to room temperature.

[0041] The conventional preparation method includes the following steps: Comparative example: The conventional preparation method was used, namely ordinary melting and casting, forging and billet opening, hot rolling, cold rolling, and annealing.

[0042] S1. Vacuum induction melting: Weigh each raw material component according to the proportion, place them in a vacuum induction melting furnace, heat them to complete melting under a protective atmosphere, and after refining and slag removal, cast them into ingots. S2. Forging and billet opening: The ingot obtained in S1 is homogenized at 1100-1200℃, and then forged into a square billet through multiple passes. The final forging temperature is not lower than 900℃, and the billet is air-cooled to room temperature after forging. S3. Hot rolling: The S2 forged square billet is heated to 1000-1150℃ and hot rolled into a hot rolled slab. The total deformation during hot rolling is 65%-75%. After hot rolling, it is water-cooled to room temperature. S4. Cold rolling: The S3 hot-rolled slab is pickled at a temperature of 50-75℃ for 9-15 minutes to remove the surface oxide scale. After that, it is cold rolled with intermediate annealing between passes at 650-700℃ for 6-8 hours. Then it is cooled in the furnace or air-cooled to room temperature to obtain the finished product.

[0043] The parameters for the homogenization process (S2) in each embodiment and comparative example are shown in Table 2; the parameters for the forging and rolling processes are shown in Table 3; and the parameters for the pickling and annealing processes are shown in Table 4. The parameters for the solution aging treatment process in each embodiment are shown in Table 5.

[0044] Table 2 Homogenization process parameters for each embodiment and comparative example

[0045] Table 3. Forging and rolling process parameters for each embodiment and comparative example.

[0046] Table 4. Pickling and annealing process parameters for each embodiment and comparative example.

[0047] Table 5. Solution treatment and aging process parameters for each embodiment.

[0048] The SEM surface morphology of the cobalt-based alloy obtained in Example 3 is shown in [Figure number missing]. Figure 1 ,Depend on Figure 1 It can be seen that the alloy surface has a uniform and dense microstructure, clear and continuous grain boundaries, and good compositional homogeneity; its metallographic structure is shown in... Figure 2 ,Depend on Figure 2 It can be seen that the alloy grains are uniform in size, equiaxed, and have straight and regular grain boundaries, indicating that the grain structure has been effectively refined and homogenized; its laser confocal morphology is shown in... Figure 3 ,Depend on Figure 3 It can be seen that the three-dimensional morphology of the alloy surface is flat with low undulation and shallow and continuous wear marks, indicating that the alloy has excellent wear resistance and anti-stripping ability at room temperature. The SEM surface morphology, metallographic structure and laser confocal morphology of the alloys obtained in the other examples are the same as those in Example 1, and will not be provided again.

[0049] The performance characterization of the cobalt-based alloys obtained in each embodiment and comparative example is shown in Table 6.

[0050] Table 6 Performance of cobalt-based alloys in various embodiments and comparative examples

[0051] As shown in Table 6, the room temperature hardness of all embodiments of the present invention is ≥500 HV10, and the wear rate is 0.8×10⁻⁶. -5 ~1.2×10 -5 mm³ / (N·m), compared to Comparative Example 1 (464 HV10, 1.6×10⁻⁶). -5 The hardness is increased by 36-116 HV10, and the wear rate is reduced by 32%-42%, with all examples showing a reduction of more than 30%.

[0052] The results show that the present invention significantly improves the hardness and wear resistance of the alloy through the synergistic strengthening of composition and the whole process. The hardness and wear rate are in a good negative correlation, which proves that the present invention has significant advantages over conventional processes and effectively solves the problems of low hardness and poor wear resistance of traditional cobalt-based alloys.

Claims

1. A wear-resistant cobalt-based alloy, characterized in that, The chemical composition and mass percentage of the cobalt-based alloy are as follows: Ni: 22-35%, Cr: 8-12%, Mo: 3-9%, Ti: 0.1-1.5%, Fe: 1%-2%, Al: 0.3-2.5%, Nb: 0.5-1.5%, C≤0.06%, B≤0.01%, P≤0.02%, Mn≤0.2%, with the remainder being Co and unavoidable impurities.

2. The wear-resistant cobalt-based alloy according to claim 1, characterized in that, The chemical composition of the cobalt-based alloy satisfies: 0.1 ≤ Ti / Al ≤ 0.6, 1.5% ≤ Fe + Nb ≤ 3%, B + P ≤ 0.02%.

3. A wear-resistant cobalt-based alloy according to claim 1 or 2, characterized in that, The cobalt-based alloy has a room temperature hardness ≥500 HV10 and a room temperature wear rate of 0.8×10⁻⁶. -5 ~1.2×10 -5 mm 3 / (N·m).

4. A method for preparing the wear-resistant cobalt-based alloy according to any one of claims 1-3, characterized in that, Includes the following steps: S1. Vacuum induction melting and casting into vacuum ingots; S2. Demold the ingot obtained in S1 and perform homogenization heat treatment; S3. Forge the ingot after S2 heat treatment into an intermediate billet; S4. Roll the intermediate billet obtained in S3 into a plate; S5. Perform pickling treatment on the board surface of the board obtained in S4. S6. Cold roll the plate after S5 pickling treatment. S7. Anneal the S6 cold-rolled sheet; S8. After S7 annealing, the board is subjected to solution aging treatment.

5. The method for preparing the wear-resistant cobalt-based alloy according to claim 4, characterized in that, The homogenization heat treatment described in step S2 involves a furnace loading temperature ≥ 500℃. After the ingot is placed in the furnace, the temperature is raised to 800℃~850℃ at a rate of 80~150℃ / h and held for 5~8h. Then, the temperature is raised to 1050~1100℃ at a rate of 50~100℃ / h and held for 10~20h.

6. The method for preparing the wear-resistant cobalt-based alloy according to claim 4, characterized in that, The forging process described in step S3 involves an initial forging temperature of 1150–1190°C, a final forging temperature of ≥900°C, and a total forging reduction of 60%–75%.

7. The method for preparing the wear-resistant cobalt-based alloy according to claim 4, characterized in that, The rolling process described in step S4 involves heating the intermediate billet to 1000-1050°C and continuously rolling it in multiple passes to obtain a hot-rolled finished sheet with a thickness of 2.0-6.0 mm.

8. The method for preparing the wear-resistant cobalt-based alloy according to claim 4, characterized in that, The pickling in step S5 involves a pickling temperature of 38–60°C and a pickling time of 3–8 minutes, followed by high-pressure water rinsing and hot air closed-loop drying to remove oxide scale and surface residue.

9. The method for preparing the wear-resistant cobalt-based alloy according to claim 4, characterized in that, The annealing described in step S7 is carried out at a temperature of 650-750°C for 2-4 hours, followed by slow cooling in the furnace.

10. The method for preparing the wear-resistant cobalt-based alloy according to claim 4, characterized in that, The solution aging treatment described in step S8 involves heating the annealed board from step S7 to 900–1000°C, holding it at that temperature for 1–2 hours, and then water-cooling it to room temperature. The first stage of aging is then performed, holding the board at 300–380°C for 3–5 hours and then furnace-cooling it to room temperature. The second stage of aging is then performed, holding the board at 520–600°C for 4–8 hours and finally furnace-cooling it to room temperature.

Citation Information

Patent Citations

  • Anti-adhesive-wear cobalt-based high-temperature alloy, key shaft and alloy preparation method

    CN118835186A

  • Metallurgical defect-free high-temperature wear-resistant cobalt-based alloy coating as well as preparation method and application thereof

    CN121653641A